THE INFLUENCE OF SPEED-STRENGTH EXERCISES ON PHYSICAL CONDITION AND THE LEVEL OF FUNCTIONAL RESERVES OF THE CARDIOVASCULAR SYSTEM (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the influence of speed-strength exercises, particularly throwing events in track and field, on the morpho-functional state, adaptive potential, and functional reserves of the cardiovascular system in young men aged 18–20 years. The relevance of the topic stems from the need to find effective means of physical education capable not only of improving physical fitness levels but also of positively influencing somatic health indicators and the adaptive capabilities of young people's organisms. The aim of the study was to determine the characteristics of the physical condition and cardiovascular system functioning in students involved in throwing events in track and field, compared to their peers attending only general physical education classes. The study involved 30 young men: 15 throwers with up to 2 years of athletic experience and 15 students in the control group. Indicators of physical development, muscle strength, the functional state of the cardiovascular system and its reserves at rest, after exertion (Martinet test), and after 5 minutes of recovery were assessed. The results showed that the student-athlete throwers had significantly higher indicators of weight, height, vital lung capacity, handgrip strength, as well as better dynamics of hemodynamic reactions. They exhibited a tendency towards circulatory economization, better physical condition index scores, and more effective recovery after physical exertion. The adaptive potential in throwers indicated stress on regulatory systems, which can be explained by the intensity of the training process. The obtained data suggest that speed-strength exercises positively influence the functional reserves of the cardiovascular system, the level of physical condition, and somatic health, and can serve as an effective means of physical education for young men.
Keywords: speed-strength exercises; throwing events; physical condition; adaptive potential; cardiac functional reserves; hemodynamics; students